Principles of Management : efficiency and effectiveness in the Private and Public Sector - Eichhorn, Peter; Towers, Ian. (Cham, Switzerland: Springer, 2018)
This textbook presents an overview of how the activities of an organisation can be managed to satisfy the needs of stakeholders through the cost effective, operationally efficient and sustainable transformation of resources into outputs. Taking an interdisciplinary approach, the authors show the relationship between management and economics and within this framework present the key areas of management activity. The book explains the connections between these areas and provides tools and instruments for successful management. The book's approach and content is relevant for all kinds of organisation - private or public sector, service or manufacturing, non-profit, large or small. Each chapter provides cases to illustrate what has been discussed and some questions to test comprehension. Throughout the book is a continuing project in which the reader is put in the position of owning their own business and must think and make decisions about what the chapter has discussed. The book combinesAnglo-American and German approaches to management and management studies, making it a valuable resource both for those who are studying management and those who are working as managers.
Chapter 1: Understanding Economic Activity -- Chapter 2: Economies and Needs -- Chapter 3: Individuals and Institutions in the Economy -- Chapter 4: A Principle for Action -- Chapter 5: Goals, Production Factors and Results -- chapter 6: The Conceptual Basis -- Chapter 7: Calculating Economic Efficiency -- Chapter 8: Economic Efficiency in Practice -- Chapter 9: Managerial Methods.
Keywords: Industrial organization; Management; Organization; Planning; Management; Industrial Organization; Organization